(untitled) (The Review of Diabetic Studies, 2024)
Introduction: One major clinical issue for surgical patients who are admitted to the hospital is surgical site infection (SSI). SSIs have a significant annual impact on surgical morbidity and mortality. Among surgical patients, surgical site infections (SSI) are the most prevalent nosocomial infection, making up 15% of all nosocomial infections. Nurses’ skills and knowledge are crucial in stopping the spread of infection. The study’s objectives were to evaluate nurses’ knowledge, attitudes, and adherence to evidence-based guidelines for preventing surgical site infections (SSIs) and to identify any factors that would encourage them to use these strategies. Settings: The study was carried out at King Abdullah Medical City (KAMC) – Mecca ;hepatobiliary surgical ward, digestive system surgical ward, and oncology surgical ward. Instruments: A questionnaire measuring nurses’ knowledge and behaviors about surgical site infection prevention, as well as a sociodemographic and work characteristics interview schedule, were used to gather data. Results: The study’s findings showed that all adherence to EBP scores were high. On the other hand, inadequate measures to avoid surgical site infections were seen. The study’s findings showed that even though the nurses surveyed had good knowledge, their behaviors were subpar, highlighting the urgent need for training programs and workshops to enhance nurses’ surgical site infection control practices. Conclusion: The results showed that while the nurses in this study knew a lot about preventing surgical site infections, their practice was lacking. Additionally, there was a favorable association between knowledge and practice in this study. Suggestions Nurses should participate in up-to-date conferences and workshops or in-service training for infection management, particularly surgical site infections.